2017
DOI: 10.1111/famp.12336
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants Coping with Transnational Deaths and Bereavement: The Influence of Migratory Loss and Anticipatory Grief

Abstract: This study examines immigrants' experiences of bereavement and coping with the deaths of family members in a transnational context. Data were collected through in-depth personal interviews with middle-aged and older immigrants from different countries of origin, who have been living in the United States for a majority of their adult lives. Thematic analysis of participants' narratives showed that immigrants' geographic distance from family complicated caregiving circumstances and rituals surrounding burial, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…Forty-four articles underwent full-text review, with 17 included in the analysis (Figure 1; Table 2). Eleven observational and six qualitative studies were identified.Most were conducted in the U.S. (Bolton & Camp, 1987;Doka, 1985;Fristad, et al , 2001;Gamino et al, 2000;Grabowski & Frantz, 1993;Nesteruk, 2018;Saler & Skolnick, 1992;Silverman, 1987;Vandercreek & Mottram, 2009;Weller et al, 1988;Zisook & DeVaul, 1983) in White Christian populations.Other country settings were Hong Kong (Chan et al, 2005;Pang & Lam, 2002), Australia (Kissane et al, 1997), Netherlands (Mitima-Verloop et al, 2019, Rwanda (Schaal et al, 2010) and Turkey (Aksoz-Efe et al, 2018). The included articles, published between 1983 and 2019, were of variable quality (Tables 3 and 4).…”
Section: The Functions Of Established Religious Communitiesmentioning
confidence: 99%
“…Forty-four articles underwent full-text review, with 17 included in the analysis (Figure 1; Table 2). Eleven observational and six qualitative studies were identified.Most were conducted in the U.S. (Bolton & Camp, 1987;Doka, 1985;Fristad, et al , 2001;Gamino et al, 2000;Grabowski & Frantz, 1993;Nesteruk, 2018;Saler & Skolnick, 1992;Silverman, 1987;Vandercreek & Mottram, 2009;Weller et al, 1988;Zisook & DeVaul, 1983) in White Christian populations.Other country settings were Hong Kong (Chan et al, 2005;Pang & Lam, 2002), Australia (Kissane et al, 1997), Netherlands (Mitima-Verloop et al, 2019, Rwanda (Schaal et al, 2010) and Turkey (Aksoz-Efe et al, 2018). The included articles, published between 1983 and 2019, were of variable quality (Tables 3 and 4).…”
Section: The Functions Of Established Religious Communitiesmentioning
confidence: 99%
“…Immigrants leave loved ones and places behind, yet they remain present in the psyche of the immigrant (Type 1, Falicov, 2002). Additionally, immigrants' loss of homeland is reflected in loss of language, foods, music, and feeling homesickness (Espin, 1987; Nesteruk, 2018). Moreover, many immigrants grieve the physical absence of their family due to not being able to visit family members because of their immigration status.…”
Section: Ambiguous Loss and The Latinx Immigrant Communitymentioning
confidence: 99%
“…A scant amount of studies examined anticipatory or disenfranchised grief among Latinx immigrants, but several studies examine complicated grief (Nesteruk, 2018). Immigrants express feelings of sadness and guilt in their inability to return to their homeland; they may experience desperation when a loved one is terminally ill, about to die, or has died (Bravo, 2017).…”
Section: Ambiguous Loss and The Latinx Immigrant Communitymentioning
confidence: 99%
“…Similar technological initiatives in performing mortuary rites have been undertaken in other countries. Virtual attendance through live streaming of the mortuary rites (Kuyvenhoven, 2020) is carried out in India (Nesteruk, 2018), UK (UK Government, 2020), Kashmir, Ireland, Canada (Hamid & Jahangir, 2020). Muslim elders above the age of 70 who used to perform the Ghusl and Kafan mortuary rites for the death have been taught how to use Skype and Zoom in instructing volunteer youth on the procedures of those death rituals from exposing them to the COVID-19 (Hirji et al, 2020).…”
Section: Effective Mechanisms Can Be Put In Place That Would Ensure Considerable Compensation Of the Established Cultural Protocols In Thmentioning
confidence: 99%